Salinity Stress and Exogenous Ascorbic Acid: Impact on Soybean Physiological Attributes and Biomass Accumulation - Ulfaturrohmah, Lu'luatul Khoiriyyah 'Ulimat; Purwanto, Edi; Supriyono, Supriyono (Universitas Panji Sakti, 2024)
Salinity, prevalent abiotic stress, has substantially restricted soybean production worldwide. This intricate environmental factor disrupts various physiological and biochemistry processes in soybean plants and ultimately diminishes yields. This experiment was conducted to report the damaging effect of sodium chloride (NaCl) given to the soil through watering at different levels (0, 50, and 100 mM NaCl) and to explore the impact of foliar spraying ascorbic acid to reduce the adverse effects of salinity at different levels (0, 400, 600, and 800 ppm). This study showed that the impact of salinity level significantly reduced gas exchange parameters, number of stomata, content of AsA, shoot dry weight, and root dry weight. The salinity also caused an increase in electrolyte leakage. Foliar application of ascorbic acid alleviated salinity-induced plant stress by increasing the number of stomata and root dry weight.